An empirical inquiry into the nature of welfarism - J. Atsu Amegashie; Bazoumana Ouattara (Center for Economic Studies and ifo Institute (CESifo), 2011)
Economists typically evaluate policies based on how such policies affect individuals' utilities. We follow this approach by taking a welfarist view of the USA's espoused policy of promoting liberty in other parts of the world. However, we take a nuanced view by investigating the type of welfare that the USA promotes. On one hand, we identify a direct value of liberty in the sense that basic human rights like freedom of speech, freedom to express one's religious beliefs, and freedom to form associations improve welfare. In this case, liberty is directly consumed. We argue that this improvement in welfare comes simply from giving people greater levels of freedom and is independent of the existence of other inputs. On the other hand, we identify an indirect value of liberty because liberty is indirectly consumed insofar as it is an input in an economy's production function and therefore affects welfare through its effect on an economy's capacity to produce goods and services. However, unlike the direct effect mentioned above, we argue that liberty alone cannot produce this indirect effect and therefore needs complementary inputs like investments in physical and human capital. We identify foreign aid as a source of information for investigating a donor's direct and indirect values of liberty. In our empirical work, our identification strategy exploits the aforementioned difference in the characteristics of the direct and indirect values of liberty to test whether the USA's foreign aid allocation is motivated by a direct value or and/or an indirect value for liberty. As a test of validity, we apply our methodology to the aid allocation of donors who, we believe, are different from the USA. These are Arab donors and Scandinavian countries (i.e., Sweden, Norway, and Denmark). We also include the UK.
Keywords: F35; H87; I38; 330; donor; foreign aid; liberty; welfarism; Demokratisierung; Freiheit; Wohlfahrtseffekt